PREVENTION OF POSTOPERATIVE LOCAL COMPLICATIONS AFTER ALLOHERNIOPLASTY IN PATIENTS WITH VENTRAL HERNIAS - Abidov Utkir (Web of Journals Publishing, 2024)
The problem of postoperative ventral hernias arose simultaneously with the birth of abdominal surgery and remains unresolved to this day. As the number of surgical interventions increases, the number of patients with postoperative hernias also increases. Their number is huge; from 2 to 15% of abdominal surgeries end in the formation of postoperative hernias [2,4,5]. Surgical treatment of hernias is not always effective, and recurrent ventral hernias form, presenting an even more difficult task for the surgeon [2,5]. Particularly difficult to solve technically are hernias that recur many times and hernias with extensive defects of the abdominal wall. The increased number of complex hernias among people of working age, the low efficiency of conventional hernia repair methods, a large number of local and general postoperative complications, frequent disability and limited performance of hernia carriers, and a decrease in the quality of life allow us to consider this problem as one of the most important socio-economic problems of practical healthcare. The correct choice of plastic method for postoperative ventral hernias is the main factor determining the results of treatment. The introduction of tension-free allohernioplasty methods has significantly improved treatment rates. The use of synthetic materials for hernioplasty, especially for large and giant ventral hernias, is associated with the absence of wound tension, which avoids increased intra-abdominal pressure and the development of abdominal compartment syndrome (cardiopulmonary disorders, intestinal paresis, relapses, etc.)[1,2 ,3].